EFEKTIFITAS KINERJA UMKM: PENTINGNYA PENGENDALIAN INTERNAL DAN ADOPSI TEKNOLOGI PAJAK - Septyana Mubarakah (Universitas Kristen Krida Wacana, 2020)
MSMEs have the highest labor absorption rate in Indonesia. The performance of MSMEs is very important to improve, because the local and national economies are very dependent on them. Aspects of internal control and adaptation of tax technology are important parts of it. This study aims to determine the effect of Internal Control and Tax Technology to the SME’s performance and to find a new measurement in the SME’s performance improvement. This research was conducted in SME’s in Tangerang area using 100 respondents. The questionnaire was used as a tool to collect data about quantitative methods with explanatory research. The results showed that generally internal control have a positive effect on SME’s performance. But separately, environment, risk assesment, information and communication possible to improve SME’s performance. While the control, supervision or monitoring activity is not. Tax technology positively improving the SME’s performance. This study recommended to adopting this model implementing for SME’s performance. Keywords: Internal Control, Tax Technology, SME’s Performance and Multi Linier Regression.